Ekstraksi Protein dari Escherichia coli BL21 Rekombinan Gen Mycobacterium tuberculosis dengan Variasi Waktu Inkubasi Induksi Isoprophyl-β-D-Thiogalactosidase (IPTG) dan Metode Lisis Sel - Nabila Swarna Puspa Hermana; Endang Kusdiyantini; Agung Suprihadi; Neny Nuraini (Jurnal Akademika Biologi, 2015)
Bacillus Calmete-Guerin vaccine is no more effective in preventing tuberculosis. The vaccine developed now is vaccine recombinant using Mycobacterium tuberculosis gen cloned in Escherchia coli to produce protein which is used as antigen compound in vaccine. The protein produced an intercellular protein which is needed cell lysis process so that the protein could be extracted. The aim of this research was to investigate the incubation time, and the optimum cell lysis method in protein recombinant extraction. Recombinant E. coli BL21 was incubated for 4, 8, 12, and 16 hours, and followed by, freeze thaw, sonication, and beads vortex lysis method. SDS PAGE quantification showed that the sample with 12 hour incubation with freeze thawing lysis method had the highest protein recombinant concentration by 4.327.870,4 pixel. Keywords: E. coli BL21 recombinant, protein extraction, enzymatic, freeze thaw, sonication, beads vortex